BIAYA PRODUKSI TAMBANG TERBUKA - Sutoyo Sutoyo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2015)
Natural resources as an economical stackeholder and energy in the world become marketcrisis caused of demanding factor is lower than production of those natural resources.Moreover the purpose of exploration is to find and acquire a maximum number of neweconomic mineral deposits within a minimum cost and in a minimum time. One of naturalresources purposed for energy is coal which decreased economic phase from practices sideand efficient uses of coal with other resources. Futhermore, all of coal firm have to reevaluatecoal production's operation such as open pit minning and revision to production of portofoliowhich could be balancing between volume and quality for more suitable for market demand.This case is one of strategies for pushing of production coal which decreasing phase becauseof increasing supply from Australia, Indonesia, Rusia as decreasing market demand.Keywords : Stakeholder, economical, production cost, coal.